Food security and economic coping strategies among fishing households: Insights from Tanjung Jabung Timur and Tanjung Jabung Barat, Jambi Province - Junaidi, Junaidi; Amril, Amril; Hardiani, Hardiani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
This study aims to: 1) Analyze the socioeconomic characteristics and economic coping strategies of fishing households in Tanjung Jabung Timur and Tanjung Jabung Barat; 2) Assess the level of food security among fishing households in these districts; 3) Examine the influence of socioeconomic characteristics and economic coping strategies on the food security of fishing households in Tanjung Jabung Timur and Tanjung Jabung Barat. Data were collected through surveys in four sample villages across the two districts. Descriptive statistics, difference tests, and Structural Equation Modeling (SEM) were employed as analytical tools. The findings indicate that economic coping strategies among fishing families, in terms of active income-generating strategies, are categorized as low. In contrast, passive strategies related to cutting back expenses are considered moderate. Overall, the level of food security among fishing households is relatively good. Furthermore, the food security level of fishing households is significantly influenced by family characteristics and coping strategies. Coping strategies directly impact and act as intervening variables between family characteristics and food security.